Alejandro Hernández, Amarás a Dios sobre todas las cosas - Anamaría González Luna (Altre Modernità, 2014)
Alejandro Hernández, Amarás a Dios sobre todas las cosas (Ciudad de México, Tusquets, 2013, 313 pp. ISBN 978-607-42-420-8) por Anamaría González Luna C.